Application of Biogas Installations as an Alternative Method to Receive Energy; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Kalashnikova T. V. Tatiana Vladimirovna (2017, 2017)
Title screen